Addressing the need to facilitate undergraduate research experiences for community college transfer students in science - Emma C. Goodwin; Katelyn M. Cooper; Logan E. Gin; Sara E. Brownell (Journal of Microbiology & Biology Education)
ABSTRACT Community college transfer students face numerous challenges, including gaining access to undergraduate research experiences. In this Perspectives piece, we articulate the benefits of undergraduate research experiences for community college transfer students, some of the common barriers for engaging transfer students in undergraduate research, and how 4-year institutions can address these problems through the development of transfer-specific programs. We specifically discuss the LEAP Scholars program, which we designed for low-income community college transfer students. The LEAP Scholars program helped students learn about undergraduate research through their participation in a science education course-based undergraduate research experience and facilitated student access to undergraduate research experiences in science faculty member research labs.